2012
DOI: 10.1136/sextrans-2012-050507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PIMA point-of-care CD4 testing in a large UK HIV service

Abstract: POCT CD4 was highly correlated with laboratory CD4 testing in this cohort, provided immediate results and was highly acceptable to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 3 publications
5
32
0
2
Order By: Relevance
“…Whereas previous studies assessed the performance of FACSCount CD48 and Pima CD4,2126,35,44,45 our study is the first independent study conducted by the WHO to evaluate the operational characteristics of these systems together with their performance, including error rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas previous studies assessed the performance of FACSCount CD48 and Pima CD4,2126,35,44,45 our study is the first independent study conducted by the WHO to evaluate the operational characteristics of these systems together with their performance, including error rates.…”
Section: Discussionmentioning
confidence: 99%
“…Misclassification of HIV patients at these thresholds may sometimes have grave outcomes. Very few studies have reported the ability of these assays to correctly classify patients at these critical thresholds 20,23,25,35. Laboratory and field evaluation of the CD4 systems is part of the prequalification of diagnostic program and is conducted after a successful review of the product dossier by the WHO.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another new entrant for POC teasing called PIMA R is being used for the measurement of T-helper cells (also known as CD4 counts). Measurement of these cells is very crucial for antiretroviral HIV therapy and monitoring of immunosuppression [40]. A descriptive list of various existing POC testing devices can be found in [41].…”
Section: Open Source Ehr/emr Systemsmentioning
confidence: 99%
“…Subsequent fluorescent image cytometry is used to obtain the CD4+ and CD8+ T cell counts. The Alere Pima CD4 counter uses a similar method to label CD4+ T cells using cartridges containing a lyophilized antibody pellet [93], [94], and has shown some success in field testing including sites in Harare, Zimbabwe [95], Maputo, Mozambique [96], Gauteng Province, South Africa [97], Kampala, Uganda [98], and London, U.K. [99]. However, in some situations, it has operational costs similar to or more expensive than standard lab flow cytometric analysis [97], [100].…”
Section: B Global Health Solutions 1) Optical Methodsmentioning
confidence: 99%